Integrasi Hermeneutika dalam Pembelajaran Anak Usia Dini: dari Pemahaman Cerita Menuju Pengembangan Karakter (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
In early childhood education (ECE), the integration of hermeneutics provides opportunities for students to cultivate positive character rooted in moral values and broaden their understanding of the meaning of stories. Hermeneutics is not only used to interpret texts; it is also a dialogical approach that encourages children to think about meaning, characters, values, and moral messages thru questioning, interpreting, and connecting stories to everyday life. The purpose of this article is to explain the concept of hermeneutics in early childhood education, how it can be applied in story-based learning, and how it impacts children's character development. The study shows that hermeneutics enhances early critical literacy, empathy, self-control, and moral choices. This article provides new guidance for educators on how to design story-based learning, which is a significant interpretive process and more than just knowledge transfer. This article provides new guidance for educators on how to create story-based learning, which is an interpretive process essential for character development, not just knowledge transfer.